The relationship of diabetes mellitus and acute coronary syndrome in Bima Public Hospital: a cross sectional study - ., Nurfitriani; Aryana, Nurfathonah (International Journal of Research in Medical Sciences, 2022)
Background: Diabetes Mellitus type II (DM) is one of risk factors of Acute Coronary Syndrome (ACS). Based on a study, hyperglycaemia can increase mortality in hospitalized patients due to ACS. Other studies also mention that there is significant relation between hyperglycaemia and incidence of ST elevation myocardial infarction (STEMI). Currently, data regarding the relationship between DM and ACS in Indonesia is still limited. The purpose of this study was to determine the relationship between the ACS and DM in inpatients at Bima public hospital, Indonesia. Methods: This study was a cross sectional study. Data were obtained from medical records of inpatients at Bima public hospital in January 2020 to December 2020. The sample was selected by consecutive sampling. All 146 patient’s data that met inclusion criteria were analysed using chi-square test. Results: The 146 patients which met inclusions criteria, as many as 85 people (58,2%) were male and 61 people (41,8%) were female. Based on age characteristics, 56 people (38,4%) were elderly and 90 people (61,6%) were adults. From 73 people diagnosed with ACS, there were 47 people (64,4%) diagnosed with DM and 26 people (35,5%) were not diagnosed with DM. Results of bivariate analysis, showed a significant relationship between DM and ACS with p value= 0.003 (OR = 2.743, 95% CI= 1.403-5.361). Conclusions: Patients with DM are 2.7 times more likely to have ACS compared to non-DM. There is statistically significant relationship between DM and ACS.